2016
DOI: 10.1159/000447543
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thrombocytopenia and Mortality in Critically Ill Patients on Continuous Renal Replacement Therapy

Abstract: Background: Both acute kidney injury (AKI) requiring dialysis and thrombocytopenia are very common and have been independently associated with mortality and morbidity in critically ill patients. Thrombocytopenia is an independent risk factor for AKI and also a marker of disease severity. There is a paucity of literature on the prevalence, incidence, and outcome of thrombocytopenia in patients receiving continuous renal replacement therapy (CRRT). We aimed at identifying the impact of thrombocytopenia on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 15 publications
5
49
0
Order By: Relevance
“…fluid overload and SIRS), the incidence of thrombocytopaenia prior to CRRT was only 26.4% . On the other hand, in a study including patients with more severe form of AKI (KDIGO criteria stage III), up to 65% of the patients had thrombocytopaenia prior to commencement of CRRT . Our study demonstrated that 48.7% of AKI patients had abnormal SOFA‐CS/thrombocytopaenia prior to RRT.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…fluid overload and SIRS), the incidence of thrombocytopaenia prior to CRRT was only 26.4% . On the other hand, in a study including patients with more severe form of AKI (KDIGO criteria stage III), up to 65% of the patients had thrombocytopaenia prior to commencement of CRRT . Our study demonstrated that 48.7% of AKI patients had abnormal SOFA‐CS/thrombocytopaenia prior to RRT.…”
Section: Discussionmentioning
confidence: 54%
“…The association of thrombocytopaenia with increased mortality in severe AKI patients has only been described in a small prospective study and in a retrospective single centre study . None of them, however, assessed the relationship with RRT treatment modification and RRT outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study showing a relationship between PCO 2 and the outcomes of patients treated with CRRT. Previous studies related to the predictive factors for survival renal recovery of the critically ill patients receiving CRRT focused on status of fluid, serum creatinine, glomerular filtration rate [10, 14, 15], coagulation functions [7, 16], inflammatory related mediators [5], and electrolyte and mineral disturbances [6]. However, there were few studies investigating parameters from respiratory system predicting survival with CRRT therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant drugs that prevent coagulation in the circuit may also affect the patient's coagulation state, increasing the risk of bleeding-induced thrombocytopenia or inducing HIT [58]. Guru et al [59] reported that thrombocytopenia occurred in 65% of critically ill patients who planned to receive CRRT, and thrombocytopenia occurred in another 20% of patients during CRRT. Patients with CRRT using heparin anticoagulation have more significant platelet decline than patients without CRRT using heparin anticoagulation.…”
Section: Preventionmentioning
confidence: 99%